2003
DOI: 10.1111/1540-8520.00032
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Absorptive Capacity and Responsiveness: An Empirical Investigation of Growth–Oriented SMEs

Abstract: This study examines the relationship between firm absorptive capacity and organizational responsiveness in the context of growth-oriented small and medium-sized enterprises (SMEs). By testing the different dimensions of absorptive capacity, external knowledge acquisition and intrafirm knowledge dissemination were found to be positively related to organizational responsiveness. In addition, the relationships between absorptive capacity and organizational responsiveness were moderated by environmental dynamism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
295
1
31

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(360 citation statements)
references
References 74 publications
14
295
1
31
Order By: Relevance
“…Some of these articles correlate the use of knowledge with its acquisition by means of relationships with parties outside the enterprise. Among them, the contributions from Yli-Renko et al (2001) and Liao et al (2003) are particularly interesting for the purposes of our present analysis. Studying the relationship with the main customer in a sample of young technology-based firms, Yli-Renko et al (2001) find that social capital (Nahapiet & Ghoshal, 1998) facilitates external knowledge acquisition, and that such knowledge is, in turn, associated positively with knowledge exploitation to gain a competitive advantage, through the development of new products, for instance.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of these articles correlate the use of knowledge with its acquisition by means of relationships with parties outside the enterprise. Among them, the contributions from Yli-Renko et al (2001) and Liao et al (2003) are particularly interesting for the purposes of our present analysis. Studying the relationship with the main customer in a sample of young technology-based firms, Yli-Renko et al (2001) find that social capital (Nahapiet & Ghoshal, 1998) facilitates external knowledge acquisition, and that such knowledge is, in turn, associated positively with knowledge exploitation to gain a competitive advantage, through the development of new products, for instance.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 96%
“…To be more precise, the items of social capital that have an impact on knowledge acquisition include: maintaining close social relationships with a key customer; personally knowing this customer's people; acquiring new customer contacts and business relationships through this key customer. Analysing a sample of growth-oriented SMEs, Liao et al (2003) find that the organizational responsiveness of these firms (reflecting the speed and coordination with which their actions are implemented and periodically reviewed) can be expected to increase if they have a well-developed absorptive capacity. Going along with Cohen & Levinthal (1990), the authors posit that absorptive capacity consists of two major components: external knowledge acquisition and internal (intrafirm) knowledge dissemination.…”
Section: Studies On Knowledge Management In Smesmentioning
confidence: 99%
“…The second of these mechanisms may be particularly important in the present context: since learning by exporting is about absorbing knowledge, often technological knowledge, from external partners, the absorptive capacity component of a firm's internal R&D expenditure may be crucial to learning by exporting. Previous research has shown that SMEs which conduct internal R&D are better able to use externally gathered information (Freel, 2000), and that SMEs with higher levels of absorptive capacity tend to be more proactive in seeking external knowledge whilst those with more modest absorptive capacity will tend to be more reactive (Liao et al 2003). In the present study we include measures of the firm's expenditure on both internal and external R&D, in order to allow as fully as possible for the R&D effect on innovation.…”
Section: Model and Variablesmentioning
confidence: 99%
“…Such relations can significantly impact on behaviour and according to Granovetter (1985: 484) are much more important 'than abstract concepts of norms or self-interest'. In general, social capital facilitates knowledge transfer, so that managing networks may be considered critical to firm performance (Liao et al 2003). However, networks function in complex and sometimes paradoxical ways (Thorpe 2005: 274).…”
mentioning
confidence: 99%